Neurotecnologie: cenni sulla dimensione biogiuridica dei “neurodiritti” - Luigi Zito (Aequitas Magazine)
The integration of artificial intelligence and neurotechnology is redefining the boundary between the human mind and the machine, opening up scenarios of great impact in the medical, educational and social fields. However, the same innovations and their pervasive use raise urgent questions on the ethical, legal and fundamental rights level, in particular regarding the so-called "neurorights". The article explores, in brief, the main current applications and future prospects, highlighting the risks related to manipulation, cognitive surveillance and the protection of mental identity (biolegal dimension). In a context of rapid technological evolution, a multidisciplinary reflection is proposed on the regulatory and cultural challenges to ensure a sustainable balance between innovation and human rights.